Embodied commons: Knowledge and sharing in Delhi's electronic bazaars. Issue 2 (March 2018) - Deka, Maitrayee
The notion of the 'sharing economy' has recently received significant academic and non-academic attention. What the different debates have in common is an emphasis on how technologically mediated knowledge and specific social motivations enable practices of sharing. This article discusses knowledge and sharing in popular marketplaces. Based on an ethnography of Delhi's electronic bazaars, Lajpat Rai market, Palika Bazaar and Nehru Place, this article suggests ways to think about knowledge that are embodied and practice-based: What is such embodied knowledge? How is it created and shared? The article argues that bazaars combine sociality established through face-to-face bargaining with informal trade arrangements to enable co-creation and collaboration around technological products. The resulting knowledge is tacit in nature and is mimetically transmitted between bodies. As a result, the bazaars feature a kind of sharing that is distinct from what is understood by most accounts of the sharing economy.